Field programmable gate array implementation of multiwavelet transform based orthogonal frequency division multiplexing system - Hadi, Suha Qasim; Jafaar, Awatif Ali; Alameri, Ban Mohammed; Malallah, Sarah Ameer (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This article offers an efficient design and implementation of a discrete multiwavelet critical-sampling transform based orthogonal frequency division multiplexing (DMWCST-OFDM) transceiver using field programmable gate array (FPGA) platform. The design uses 16-point discrete multiwavelet critical-sampling transform (DMWCST) and its inverse as main processing modules. All modules were designed using a part of Vivado® Design Suite version (2015.2), which is Xilinx system generator (XSG), and is compatible with MATLAB Simulink version R2013b. The FPGA implementation is carried out on a Zynq (XC7Z020-1CLG484) evaluation board with joint test action group (JTAG) hardware co-simulation. According to the results obtained from the implementation tools, the implemented system is efficient in terms of resource utilization and could support the real-time operations.